Characteristic aspects os perimolysis: a literature review between the years 2010 to 2021 (Research, Society and Development, 2021)
The aim of the present work was to present an exploratory literature review on the topic of perimolysis, due to the difficulty in diagnosing this pathology. The literature review included articles published between 2010 and 2021, using virtual health databases, such as: Academic Google, SciELO and PubMed. In Dentistry, tooth wear is commonly found in routine clinical examinations, has different forms and occurs in specific dental regions, having a multifactorial etiology. Dental erosion has its etiology in an extrinsic or intrinsic way, in the latter case, it is usually called perimolysis. It is characterized by progressive acid demineralization of tooth structure without bacterial involvement, occurring from endogenous chemical agents directly linked to vomiting/belching/regurgitation of stomach contents into the esophagus, which reaches the oropharynx and oral cavity, affecting the enamel and the dentin. Diagnosis can be controversial and challenging, as it can be confused with other types of dental injuries, or go unnoticed in early stages. It is extremely important to emphasize the participation of the dentist in this diagnosis, which is directly linked to patients with eating disorders such as Bulimia and Anorexia nervosa. It was concluded that perimolysis is often associated with eating disorders, has a slow progression, with often subtle signs, which usually causes failure in early diagnosis, requiring knowledge of the pathology and its etiological factors, so that the professional is able to perform such diagnosis, managing to avoid progression to advanced stages and consequently more complex treatments.